Breast Brachytherapy and a Case Report - ALSAN ÇETİN, İLKNUR (KARE PUBL, 2019)
For women who had breast-conserving surgery (BCS), brachytherapy can be used along with external beam radiation as a way to add an extra boost of radiation to the tumor site. It may also be used as a form of accelerated partial breast irradiation. Tumor size, location and other factors may affect brachytherapy decision. The patient was 47 years old and applied to Istanbul University Oncology Institute Radiation Oncology Department. A mass in the upper outer quadrant was detected. Invasive ductal cancer was diagnosed with biopsy. MKC and sentinel lymph node biopsy were performed in 2013. Histological and nuclear grade II, ER (+++), PG (+++), cerbB2 (-), lympho vascular invasion (-), pT1N0 was revealed. In 2013, 50 Gy/25 frx ERT was applied to the left breast tangent. After 16 days, HDR was performed twice daily (BID) (4x3Gy), 14-channel ISI breast implants. The reference dose is defined as 3 Gy GTV.
Keywords: Brachytherapy; breast cancer; 20-YEAR FOLLOW-UP; IN-SITU CARCINOMA; CONSERVING SURGERY; FEMALE BREAST; IRRADIATION; CANCER; MASTECTOMY; THERAPY; PHASE-3; TRIAL